Food Protein-Induced Allergic Proctocolitis: The Effect of Maternal Diet During Pregnancy and Breastfeeding in a Mediterranean Population - Vassilopoulou, Emilia; Feketea, Gavriela; Konstantinou, George N.; Zekakos Xypolias, Dimitris; Valianatou, Mina; Petrodimopoulou, Maria; Vourga, Vasiliki; Tasios, Ioannis; Papadopoulos, Nikolaos G. (Frontiers in Nutrition, 2022)
Background: The aim of the current investigation was to explore the association of food protein induced allergic proctocolitis (FPIAP) in Greek infants with the maternal diet during pregnancy and breastfeeding. Methods: A multicenter retrospective case-control study was conducted in 6 regions in Greece, with 96 mothers of infants with, and 141 mothers of infants without a history of FPIAP. Maternal dietary habits during pregnancy and breastfeeding were evaluated with validated questionnaires: a) The Mediterranean Diet (MedDiet) Score, and b) The Mediterranean Oriented Culture Specific Semi-Quantitative Food Frequency Questionnaire. Statistical testing, modeling and exploration of the FPIAP risk in relation to the maternal diet using elastic net regression models were performed with R software and Studio. Results: FPIAP was associated with cow’s milk (83.6%), egg (7.3 %), and wheat, beef (6.4%) in the maternal diet. Adherence to MedDiet was similar among the mothers, but mothers of FPIAP infants consumed more vegetables and olive oil. Elastic net prediction models showed that, in this Mediterranean population, increased consumption during pregnancy and lactation of common allergens, whole grain products, homemade food, fish and shellfish, fruit was associated with a decreased risk of FPIAP; conversely, a high intake of vegetables, sugar and total fat, and non-stick/grilled cooking, were associated with increased risk of FPIAP, as was high intake of salt and white flour during lactation. Conclusions: Components of a maternal MedDiet may protect against FPIAP when traditional cooking methods are adopted and fish, fruit and whole wheat products are consumed frequently during pregnancy and breastfeeding.